Biomimetic flavin-catalysed reactions for organic synthesis. Issue 28 (28th July 2015) - Iida, H.; Imada, Y.; Murahashi, S.-I.
<x xml:space="preserve">Abstract</x> Using simple riboflavin related compounds as biomimetic catalysts, catalytic oxidation of various substrates with hydrogen peroxide or molecular oxygen can be performed selectively under mild conditions. The principle of these reactions is fundamental and will provide a wide scope for environmentally benign future practical methods.